Measuring the Blood Sugar Level and Time (BSLT) using Mobile Strategy to Remote Monitoring of DIABETES Chronic Diseases for Children in North African Countries - Sheta, Osama E.; Omer, Majzoob Kamal Aldein; Elkhtem, Mohamed Sir (British Journal of Healthcare and Medical Research, 2015)
chronic diseases for children such as DIABETES is a challenge for parents in all third world countries. Especially that percentage of giving birth to children with chronic diseases is increasing dramatically in North African countries. Thus the official task of parents to help their children in how to live and deal the condition with this chronic disease. In this paper we propose a child DIABETES monitoring system which is integrated sensors and smart phone to facilitate the management of chronic disease - DIABETES. The system automatically collects physical signs, such as Blood Glucose level. It allows users, especially children with diabetes to conveniently record daily test results and track long term health condition changes regardless of their locations. All the procedures are performed automatically without entering the user (Patient) any data on the system manually. Of the most important objectives of the application is help the parents to monitoring the level of sugar in the blood for their child at any time and alert them automatically to any risk